2020
DOI: 10.5298/1081-5937-48.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Frequency Assessment: The Challenge of Standardizing Heart Rate Variability Biofeedback Research

Abstract: The resonance frequency (RF) is the rate at which a system, like the cardiovascular system, can be activated or stimulated for maximal variability. Precise RF measurement is needed to standardize training protocols to help researchers determine the importance of RF breathing in achieving clinical and optimal performance outcomes. Lehrer and colleagues have developed and standardized a psychometrically reliable RF measurement protocol that can facilitate training and replication. This article provides a detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…If your clients entered training to lower blood pressure, consider the rate that produces the greatest decreases. In response to the previous example, breathing at 5.0 bpm reduced blood pressure by 9/12 mmHg compared with 5.5 bpm (Shaffer, 2020). When you collaborate with your clients to break ties, you can strengthen your relationship and increase the likelihood that they will practice resonance frequency breathing outside of the clinic.…”
Section: How To Break Ties and Confirm The Resonance Frequencymentioning
confidence: 95%
See 2 more Smart Citations
“…If your clients entered training to lower blood pressure, consider the rate that produces the greatest decreases. In response to the previous example, breathing at 5.0 bpm reduced blood pressure by 9/12 mmHg compared with 5.5 bpm (Shaffer, 2020). When you collaborate with your clients to break ties, you can strengthen your relationship and increase the likelihood that they will practice resonance frequency breathing outside of the clinic.…”
Section: How To Break Ties and Confirm The Resonance Frequencymentioning
confidence: 95%
“…Skin conductance level (SCL) is a tonic measure of eccrine sweat gland activity. Furthermore, an EMG , which monitors skeletal muscle action potentials, can likewise indicate dysfunctional breathing if frontales or breathing accessory muscles exceed normal resting values of ≤3 microvolts (μV; Shaffer, 2020 ). For example, elevated frontales, scalene, or trapezius EMG activity may signal excessive breathing effort ( Khazan, 2013 ).…”
Section: A Resonance Frequency Assessment Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the frequency of breathing where the oscillation of heart rate due to the respiratory sinus arrhythmia (produced by the slow breathing) resonates with the oscillation in heart rate due to the baroreflex. This results in a maximal heart rate variation, and a maximal increase in baroreflex gain with an increase in baroreflex gain at resting states after consistent practice as well (Vaschillo, Vaschillo, and Lehrer 2006; P. M. Lehrer et al 2003;Fredric Shaffer 2020). The research into the benefit of employing resonance frequency into biofeedback training is limited, although an analogue study conducted in 2017 found that using a resonant frequency compared to a standardised breathing frequency was associated with a higher positive mood and a significantly higher LF/HF HRV ratio (Steffen et al 2017).…”
Section: Resonance Frequencymentioning
confidence: 95%